Income and Price Elasticities for Exports of Developing Countries - Marquez, Jaime; McNeilly, Carlyl (The Review of Economics and Statistics, 1988)
Income and price elasticities for non-oil exports of non-OPEC developing countries play an imp ortant role in the development of policy responses to the debt crisis. These elasticities are estimated for the major Standard Internation al Trade Classification commodity groups. Based on two-stage least sq uares and quarterly data for 1973 to 1984, the income elasticity for non-oil exports ranges between 1.4 and 1.9. The analysis also tests t he properties of the error term, the dynamic specification, and para- metric stability. The sensitivity of the results is assessed using Sh iller's lags and band spectrum estimation. Copyright 1988 by MIT Press.